2020
DOI: 10.1038/s41421-020-00200-x
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptome atlas of lung adenocarcinoma featured with ground glass nodules

Abstract: As an early type of lung adenocarcinoma, ground glass nodule (GGN) has been detected increasingly and now accounts for most lung cancer outpatients. GGN has a satisfactory prognosis and its characteristics are quite different from solid adenocarcinoma (SADC). We compared the GGN adenocarcinoma (GGN-ADC) with SADC using the single-cell RNA sequencing (scRNA-seq) to fully understand GGNs. The tumor samples of five patients with lung GGN-ADCs and five with SADCs underwent surgery were digested to a single-cell su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 52 publications
5
70
0
Order By: Relevance
“…Second, capillary ECs in healthy lung expressed a gene signature of semi-professional antigen-presenting cells, but these immunomodulatory ECs are underrepresented in lung tumors [ 6 ]. In agreement, genes related to antigen presentation and chemotaxis were downregulated in TECs from SADC compared to early-stage GGN-ADC [ 83 ]. On the other hand, ECs with transcriptomic features of high endothelial venules (HEVs) were more abundant in tumors [ 84 ], suggesting a complex regulation of tumor immunity by TECs.…”
Section: Ec Heterogeneity In Cancermentioning
confidence: 63%
See 2 more Smart Citations
“…Second, capillary ECs in healthy lung expressed a gene signature of semi-professional antigen-presenting cells, but these immunomodulatory ECs are underrepresented in lung tumors [ 6 ]. In agreement, genes related to antigen presentation and chemotaxis were downregulated in TECs from SADC compared to early-stage GGN-ADC [ 83 ]. On the other hand, ECs with transcriptomic features of high endothelial venules (HEVs) were more abundant in tumors [ 84 ], suggesting a complex regulation of tumor immunity by TECs.…”
Section: Ec Heterogeneity In Cancermentioning
confidence: 63%
“…Surprisingly, genes involved in antigen presentation (MHC class I and II), chemotaxis ( CCL2 , CCL18 , IL6 ), and immune cell homing ( ICAM1 ) were downregulated in TECs compared to normal lung ECs, raising the question whether TECs potentially contribute to immune tolerance [ 81 ]. In agreement, compared to early-stage ground glass nodules adenocarcinoma (GGN-ADC), TECs from late-stage solid adenocarcinoma (SADC) exhibited lower levels of genes involved in antigen presentation and chemotaxis [ 83 ].…”
Section: Ec Heterogeneity In Cancermentioning
confidence: 88%
See 1 more Smart Citation
“…We further investigated how Tns1 high fibroblasts interacted with CD8 + T cell in the TME based on aforementioned single-cell RNA sequencing data of mouse esophageal cancer model. We classified CD8 + T cells into 6 clusters (Supplementary Figure 12A) , including four clusters of naive T cells (Tn), one cluster of cytotoxic T cell (Ct), and one cluster of exhausted T cell (Ex) according to canonical markers (Supplementary Figure 12B) [ 49 , 67 , 68 ]. Then, we used CellChat to infer the cell-cell communication network among CD8 + T cells and Tns1 high fibroblasts [52] .…”
Section: Resultsmentioning
confidence: 99%
“…As a kind of important tumor-infiltrating lymphocytes (TILs), low-expressed NK cells are discovered on multiple cancers, which are linked with a poor prognosis of patients, too ( 42 , 43 ). A single cell sequencing study of lung GGO and solid nodules concluded that NK cell cytotoxicity was lower in solid nodules, which showed that the function of the NK cell decreased during the progression of lung adenocarcinoma ( 44 ). Mechanism researches also indicate the functional improvement of NK cells may induce tumor regression ( 36 , 45 ).…”
Section: Discussionmentioning
confidence: 99%